1986
DOI: 10.1177/0305735686141002
|View full text |Cite
|
Sign up to set email alerts
|

The Pleasingness of Melodic Sequences: Contrasting Effects of Repetition and Rule-familiarity

Abstract: Twenty melodic tone sequences varying in harmonic structure were first presented once each to listeners selected from three different levels of previous musical training. Listeners rated each sequence on a 6-point scale of "pleasingness". Next, 5 sequences from the original set of 20 were each repeated 10 times in a row and rated after each repetition. The 5 sequences were assigned to listeners so that across listeners the 20 original sequences were equally represented. Finally, all 20 sequences were again eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1
2

Year Published

1987
1987
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 23 publications
1
24
1
2
Order By: Relevance
“…The second alternative explanation is the role of familiarity, which is known to decrease the perceived complexity of stimuli (Smith and Cuddy, 1986;North and Hargreaves, 1995). The African group was familiar with some of the western melodies but the western group was not familiar with any African melodies.…”
Section: Discussionmentioning
confidence: 99%
“…The second alternative explanation is the role of familiarity, which is known to decrease the perceived complexity of stimuli (Smith and Cuddy, 1986;North and Hargreaves, 1995). The African group was familiar with some of the western melodies but the western group was not familiar with any African melodies.…”
Section: Discussionmentioning
confidence: 99%
“…With this re-analysis in mind, however, the results of three of the four pieces do not support a strictly increasing relationship. Subsequent literature has reported that peak enjoyment may occur after much fewer than 25 exposures (Bartlett, 1973;Getz, 1966;Heyduk, 1975;Krugman, 1943;Smith & Cuddy, 1986) which Notes.…”
Section: Re-analyzed Datamentioning
confidence: 99%
“…Berlyne emphasized the relevance of information complexity to the appreciation of music, suggesting that for each individual, there is an optimal level of structural complexity that gives rise to a moderate and hence desirable level of physiological arousal (15]. Some empirical support for Berlyne's optimal-complexity model has been provided for musical stimuli by Smith and Cuddy [16].…”
Section: Emotional Responses To Musicmentioning
confidence: 99%